DNA-hydrolysing activity of IgG antibodies from the sera of patients with schizophrenia. Issue 9 (September 2015) - Ermakov, Evgeny A.; Smirnova, Ludmila P.; Parkhomenko, Taisiya A.; Dmitrenok, Pavel S.; Krotenko, Nina M.; Fattakhov, Nikolai S.; Bokhan, Nikolay A.; Semke, Arkadiy V.; Ivanova, Svetlana A.; Buneva, Valentina N.; Nevinsky, Georgy A.
Abstract : It is believed that damage to the membranes of brain cells of schizophrenia (SCZ) patients induces the formation of autoantigens and autoantibodies. Nevertheless, the importance of immunological changes leading to the loss of tolerance to self-antigens in the genesis of SCZ has not been established. The MALDI mass spectra of the IgG light chains of 20 healthy donors were relatively homogeneous and characterized by one peak with only one maximum. In contrast to the healthy donors, the MALDI mass spectra of IgG light chains corresponding to 20 SCZ patients demonstrated, similarly to 20 autoimmune systemic lupus erythematosus (SLE) patients, two maxima of a comparable intensity. In addition, the MALDI spectra of the IgG light chains of five SLE and four SCZ patients contained a small additional brightly pronounced peak with remarkably lower molecular mass compared with the main one. DNase autoantibodies (abzymes) can be found in the blood of patients with several autoimmune diseases, while the blood of healthy donors or patients with diseases without a significant disturbance of the immune status does not contain DNase abzymes. Here, we present the first analysis of anti-DNA antibodies and DNase abzymes in the sera of SCZ patients. Several strict criteria have been applied to show that the DNase activity is an intrinsic property of IgGs from the sera of SCZ patients. The sera of approximately 30% of SCZ patients displayed a higher content of antibodies (compared with 37% of SLE) interacting with single- and double-stranded DNA compared with healthy donors. Antibodies with DNase activity were revealed in 80% of the patients. These data indicate that some SCZ patients may show signs of typical autoimmune processes to a certain extent.